The positive effect of antibiotic paromomycin compared with kanamycin for selection of transgenic plants with NPTII gene on the example of Nicotiana tabacum - Nitovska, I.O.; Avilov, I.D.; Morgun, B.V. (Фактори експериментальної еволюції організмів, 2015)
Aims. To investigate the efficiency of antibiotic paromomycin as a selective agent for the production of transgenic plants
with nptII gene compared with kanamycin sulfate on the example of Nicotiana tabacum. Methods. A vector containing
the nptII gene under the control of 35S promoter of cauliflower mosaic virus was used in Agrobacterium-mediated genetic
transformation of leaf explants from Nicotiana tabacum. Following parallel explant selection on media with paromomycin
or kanamycin plant regeneration was observed. Total DNA of the regenerated plants was tested for the presence of nptII
gene by PCR. Results. It has been shown that the use of antibiotic paromomycin is effective for obtaining transgenic
tobacco plants. Paromomycin revealed a softer effect on plant explants compared with kanamycin sulfate without causing
severe depression on regenerative ability of plant tissues, leading to a higher frequency of regeneration on selective
medium and transformation. Conclusions. Transgenic tobacco plants were received on selective media containing
paromomycin with high frequency. Due to the mild effects on plant explants, paromomycin is an attractive agent for
selection of transgenic plants with nptII gene, especially for those species in which the kanamycin sulfate has a strong
negative impact on the regenerative potential.
Keywords: Paromomycin, kanamycin, nptII, Nicotiana tabacum, selection of transgenic plants.